Effect of graphene oxide or triethanolamine-modified graphene oxide on the hydration of calcium sulfoaluminate cement. (22nd August 2022) - Yang, Fengming; Xie, Jiateng; Wang, Weijie; Wang, Wenlong; Wang, Zengmei
Graphical abstract: Highlights: GO and TGO can play a catalytic role in the hydration process of CSA. Fewer carboxyl groups and the steric hindrance effect of TGO result in better dispersion in CSA. The greater water storage capacity of TGO can facilitate the later hydration of CSA. Abstract: To meet the urgent demand of ultra-early strength cementitious materials for modern infrastructure, this work explored the preparation of ultra-early strength cementitious materials based on calcium sulfoaluminate cement (CSA) from solid waste with 3% graphene oxide (GO) (named G3 sample) and 3% triethanolamine (TEOA) modified GO (TGO) (named TG3 sample). The results show that CSA doped with TGO has more potential to prepare ultra-early strength cementitious materials, which originated from the better dispersion of TGO in CSA paste, caused by the fewer –COOH group and more –OH group branched chains in TGO with an enhanced steric hindrance effect. Compared with the blank group, the initial setting times of G3 and TG3 were decreased by 11.90% and 26.19%, respectively, while for the compressive strength at 3 h and 28d, the G3 sample was increased by 253.4% and 6%, respectively, while for TG3 it was 294.9% and 23.38%. This is due to the better dispersion of TGO in the CSA paste and better storage capacity of water molecules, which results in a significant catalytic effect on the early hydration as well as the later continuous hydration of CSA. Meanwhile, the ability of TGO to effectively refine the pores and micro-cracks in the cement matrix also contributes to its strength. In addition, the hydration kinetics of TG3 at different reaction stages demonstrated that the activation energy needed for each order reaction section of hydration was obviously reduced, resultantly, the hydration reaction occurred easily.